Translation, Medical Humanism and Early Modern Prose Fiction: Science and Literature in Francisco López de Villalobos. Issue 3 (March 2018) - Fernández, José María Pérez
Abstract : Francisco López de Villalobos (1473–1549) shared an interest in translation with fellow humanist physicians like Andrés Laguna or François Rabelais. His Spanish rendering of Plautus's Amphitryon was first published in 1517 (Alcalá: Brocar) and then printed again as part of Los problemas de Villalobos (Zamora: Musetti, 1543). Alongside Plautus's comedy, the reader could find in this new volume moral and political treatises, essays on natural philosophy, dialogues peppered with comic stories, autobiographical sketches, and passages that verged on the picaresque. Its tragicomic satura of serious and humorous matter, its combination of poetry, dialogue, narrative episodes and essayistic prose turns Los problemas into a fascinating text that defies categorization. This article aims to explore how this singular admixture responded to a growing demand from an increasing readership that sought to be both enlightened and amused, and how it also pointed to the development of prose fiction as a protean genre.